Challenges faced by midwives in the implementation of facility-based maternal death reviews in Malawi - Mercy Dokiso Chirwa; Juliet Nyasulu; Lebitsi Modiba; Makombo Ganga- Limando (BMC, 2023)
Abstract Background Maternal death reviews provide an in-depth understanding of the causes of maternal deaths. Midwives are well positioned to contribute to these reviews. Despite midwives' participation as members of the facility-based maternal death review team, maternal mortality continues to occur, therefore, this study aimed to explore the challenges faced by midwives as they participate in maternal death reviews in the context of the healthcare system in Malawi. Methods This was a qualitative exploratory study design. Focus group discussions and individual face-to-face interviews were used to collect data in the study. A total of 40 midwives, who met the inclusion criteria, participated in the study. Data was analyzed manually using a thematic content procedure. Results Challenges identified were: knowledge and skill gaps; lack of leadership and accountability; lack of institutional political will and inconsistency in conducting FBMDR, impeding midwives' effective contribution to the implementation of maternal death review. The possible solutions and recommendations that emerged were need-based knowledge and skills updates, supportive leadership, effective and efficient interdisciplinary work ethics, and sustained availability of material and human resources. Conclusion Midwives have the highest potential to contribute to the reduction of maternal deaths. Practice development strategies are required to improve their practice in all the areas they are challenged with.